EVALUATION OF ANTI-INFLAMMATORY, ANALGESIC, AND ANTIPYRETIC EFFECT OF ETHANOLIC EXTRACT OF PEDALIUM MUREX LINN. FRUITS - Patel, Mahendra K; Mandavia, Divyesh R; Patel, Tejas K; Barvaliya, Manish J; Tripathi, Chandrabhanu (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
This study investigated the possible anti-inflammatory, analgesic, and antipyretic effects of ethanolic extract of Pedalium murex Linn. fruits, in selected experimental animal models. Anti-inflammatory activity of Pedalium murex Linn. with doses of 200 mg/kg and 400 mg/kg, p.o., was evaluated by λ-carrageenan induced paw oedema in wistar albino rats; analgesic activity with doses of 280 mg/kg and 560 mg/kg, p.o., was evaluated by hot plate method and acetic acid induced writhing method in swiss albino mice; and antipyretic activity with doses of 110 mg/kg and 220 mg/kg, p.o., was evaluated in Newzealand white rabbits by injecting gram –ve lipopolysaccharide obtained from E. coli. Results were analyzed by one way ANOVA followed by Dunnet’s multiple comparison test. Pedalium murex Linn. showed significant anti-inflammatory activity from 15 min to 180 min as compared to vehicle treated animals. It was comparable to diclofenac sodium at 180 min. It did not prolong the reaction time on hot plate method but significantly reduced the number of writhing after acetic acid administration. It didn’t show any antipyretic activity on lipopolysaccharide induced pyrexia. Ethanolic extract of Pedalium murex Linn. fruits have an anti-inflammatory and peripheral analgesic effects.